THE IMPACT OF PSAK 71 IMPLEMENTATION ON THE FINANCIAL PERFORMANCE OF BANKING COMPANIES IN INDONESIA (A CASE STUDY ON INDONESIA CONVENTIONAL BANK 2017 – 2022) - Ahmad Robbani; Lin Oktris (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the impact of the implementation of PSAK 71 on the formation of CKPN and its effect on the financial performance of banking companies in Indonesia. Financial performance is measured using the CAR, KAP, NPM, BOPO, ROA, and LDR ratios. The sample consists of banking financial institutions or conventional banking companies whose data were available on the Indonesia Stock Exchange before the implementation of PSAK 71, specifically under PSAK 55 from 2017 to 2019 and those that had implemented PSAK 71 from 2020 to 2022. The sample selection was conducted using the purposive sampling method, and the analysis was done using the CAMEL method along with descriptive statistical analysis. The results of this study show that in the comparison of financial performance, as measured using the CAR, KAP, NPM, ROA, and LDR ratios, there is a significant difference between the period before and after the implementation of PSAK 71. However, the BOPO ratio does not show a significant difference.